2017
DOI: 10.1902/jop.2016.160288
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin Inhibits Interleukin (IL)‐8 and IL‐6 Production in Human Coronary Artery Endothelial Cells Stimulated With Aggregatibacter actinomycetemcomitans Serotype b

Abstract: These results suggest Aa-induced proinflammatory endothelial responses are regulated by rosuvastatin in a mechanism that appears to involve KLF2 activation. Use of rosuvastatin to prevent cardiovascular disease may reduce risk of endothelial activation by bacterial antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 52 publications
1
25
0
1
Order By: Relevance
“…Of interest, this effect seemed to be mainly driven by IL-6 and IL-8 ( Fig. 2), two of the most studied cytokines in the atherosclerotic process and already associated to the statin related benefit in experiments conducted on coronary artery endothelial cells [29,30]. A similar trend for statin induced IL-6 and Il-8 reduction, although not statistically significant, was found in vivo.…”
Section: Discussionmentioning
confidence: 64%
“…Of interest, this effect seemed to be mainly driven by IL-6 and IL-8 ( Fig. 2), two of the most studied cytokines in the atherosclerotic process and already associated to the statin related benefit in experiments conducted on coronary artery endothelial cells [29,30]. A similar trend for statin induced IL-6 and Il-8 reduction, although not statistically significant, was found in vivo.…”
Section: Discussionmentioning
confidence: 64%
“…The chemokines IL-8 and MCP-1 have been reported as key inflammatory chemokines that induce chemotactic and stimulatory responses and promote monocyte and endothelial cell interactions (31,32). Lipopolysaccharide derived from enterobacteria induces the expression of these chemokines in HCAECs; however, in models with periodontopathogens, studies of LPS have been limited to P. gingivalis and A. actinomycetemcomitans (22,33). Our results showed a relevant endothelial inflammatory response, as E. corrodens-LPS mainly increased IL-8 and MCP-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of MCP‐1, RANTES, MIP‐1α, IL‐8, and GM‐CSF were measured in culture supernatants from HCAECs stimulated with LPS for 6, 12, 24, or 48 h by flow cytometry using a Human Pro‐inflammatory Chemokine Panel (BioLegend, San Diego, CA, USA) according to the manufacturer's instructions. The minimum detectable concentrations of IL‐8, MCP‐1, RANTES, MIP‐1 α , and GM‐CSF were 1.9, 2.2, 3.6, 2.6, and 2.0 pg ml −1 , respectively . Flow cytometry was performed using the BD Accuri C6 flow cytometer (Becton Dickinson Biosciences, San Jose, CA, USA), and the data were processed using BD Accuri C6 Software (Becton Dickinson Biosciences).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence indicates that the interactions between bacteria and ECs play an important role in the pathogenesis of endothelial dysfunction. However, in vitro studies with EC cultures have shown that Pg‐LPS does not induce strong expression of markers of the inflammatory response, while LPS from Aggregatibacter actinomycetemcomitans (Aa) and Eikenella corrodens does (Erridge, Spickett, & Webb, ; Gualtero et al, ; Ho, Guo, Chunga, Goodwin, & Xie, ; Kebschull, Demmer, & Papapanou, ; Viafara‐Garcia, Gualtero, Avila‐Ceballos, & Lafaurie, ). In these two‐dimensional (2D) models, cultured ECs are not exposed to the components of the basement membrane that underlie the endothelium.…”
Section: Introductionmentioning
confidence: 99%